Can a City Become Truly Smart Without Involving All Groups of Stakeholders: a Discussion Based on the Example of “Acoustical Smartening” - KAŹMIERCZAK, Jan (Architecture, Civil Engineering, Environment, 2025)
The article presents the problem of transforming urbanized space into a so-called “smart” space, paying special attention to the participation of space users in such transformation processes. In the initial part of the article, the author briefly presents a subjective overview of the ways of perceiving the idea of a “Smart City” (chapter 2). The next part (chapter 3) is devoted to a detailed description of urban space user groups, considering not only city residents but also people temporarily staying in the city. Then, based on the conducted research on urban space users, an attempt was made to identify the willingness and scope of involvement of urban space users in the processes of making such space “smart”. Then, specific acoustic phenomena related to the functioning of the urban organism were selected as the area of acoustic phenomena related to the city. The basic assumptions and research methods conducted in this problem area are presented, and selected conclusions from this research are shown. In conclusion, the author presents his intentions for further study of the issues discussed in the article.